Performance Evaluation of a Mobile Attendance System Using Dual-Factor Dynamic Qr Code and Gps Geofencing - Rosma Siregar; Bagoes Maulana; Muhammad Isnaini; Elsa Sabrina; Harvei Desmon Hutahaean (Cattleya Darmaya Fortuna, 2026)
This study develops and evaluates an Android-based attendance system integrating dual-factor authentication using dynamic QR codes and GPS geofencing to prevent proxy attendance in higher education. The system was developed using the Waterfall model and evaluated through quantitative experiments measuring response time, GPS accuracy drift, and security robustness via Black-Box testing. Results show high efficiency with an average response time below 1.5 seconds. GPS validation achieved an average drift of 4.2 meters outdoors and 12.5 meters indoors, remaining within the 30-meter geofencing threshold. The system successfully rejected unauthorized attempts, including out-of-range scans and fake GPS spoofing. These findings demonstrate that combining dynamic QR codes with GPS validation significantly improves attendance authenticity and system reliability compared to single-factor methods. The study provides empirical evidence of a robust and scalable solution for secure mobile-based attendance systems in higher education.